Real and Nominal Exchange Rates in the Long Run - Adams, Charles (IMF Working Papers; Working Paper ;, 1991)
This paper decomposes longer-run movements in (major) dollar real exchange rates into components associated with changes in nominal exchange rates and price levels, and their comovements. Though the decompositions suggest some permanent movements, they imply that there are large transitory components in real exchange rates. These transitory components in real exchange rates are found to be closely associated with those in nominal exchange rates. A stochastic version of Dornbusch's overshooting model-configured with representative parameter values for the United States and subjected to permanent nominal shocks-can rationalize these transitory comovements of nominal and real exchange rates as well as several other features of the decompositions.